Potential of Vetiver Grass for Erosion Control and Slope Stabilization in Sylhet Region of Bangladesh: Slope Stabilization and Erosion Control by Vetiver (Journal of the Sylhet Agricultural University, 2025)
Slope stability analysis is critical for evaluating terrain stability, enabling the identification of preventive measures and the prediction of potential failures. This experimental study, conducted at Sylhet Agricultural University, investigates the effectiveness of vetiver grass in reducing soil erosion and improving slope stability through factor of safety calculations. A physical model representing an earthen slope with and without vetiver was developed on campus. Results showed that soil erosion decreased by 75.60% to 77.46% with vetiver compared to bare soil. Using effective stress analysis numerical method and GeoStudio software, the factor of safety was computed for sandy clay samples, where the unit weights of bare and vetiver-rooted soils were 18 kN/m³ and 17.3 kN/m³, and average cohesion values were 15 kN/m² and 25 kN/m², respectively. The factor of safety for bare and vetiver-rooted soil is 1.73 and 2.55, respectively indicating that vetiver enhances slope stability by approximately 1.48 times. These findings demonstrate that vetiver grass is an effective and sustainable option for erosion control and slope stabilization in Sylhet.J. Sylhet Agril. Univ. 12(1): 142-152, 2025